Siskohat Sebagai Inovasi Manajemen Dakwah: Upaya Modernisasi Administrasi Haji di Era Society 5.0 - Lestari, Siti Kris Fitriana Wahyu; Shodiqoh, Mira (ASWALALITA: Journal of Da'wah Management, 2025)
This study aims to analyze the role of the Integrated Hajj Information and Computerization System (Siskohat) as an innovation in da’wah management within the modernization of hajj administration in Indonesia during the Society 5.0 era. Siskohat is viewed not merely as an administrative tool but also as a transformative da’wah medium that emphasizes transparency, accountability, and technology-based services. Employing a qualitative approach through library research, this study explores the integration between da’wah management and the digitalization of hajj bureaucracy. The findings indicate that the implementation of Siskohat enhances the effectiveness of pilgrim data management, accelerates administrative processes, and provides broader access to information for the public. Furthermore, the utilization of Siskohat aligns with the principles of da’wah management, which prioritize community service (khidmah al-ummah) through technological innovation. The study concludes that Siskohat represents a strategic innovation in realizing modern, adaptive, and pilgrim-oriented hajj governance in the Society 5.0 era, and serves as a model for digital-based da’wah management practices in Indonesia.